Readiness of adolescents for self-preservation of health in the information educational space - Kapalygina, I.I.; Voloshin, L.N.; Kondakov, V.L.; Kopeikin, E.N. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identifying the level of readiness of schoolchildren to maintain health in the information and educational space. Methods and structure of the study. Pedagogical research (stating stage) was conducted on the basis of schools in Grodno (Republic of Belarus), which was attended by 324 schoolchildren aged 14-15 years. Research methods: theoretical analysis and generalization of scientific data; empirical methods (survey, questioning); methods of mathematical statistics (correlation analysis). Results and conclusions. Analysis of self-assessment of the level of readiness of students aged 14-15 for self-pres- ervation of health (cognitive and activity components) in the information and educational space indicates the presence of serious problems. Namely, more than half of adolescents have an insufficient level of knowledge about information hygiene, security, and a healthy speech environment. 2/3 of the respondents confirm that they are not ready to take meaningful ac- tions to use knowledge about maintaining health. At the same time, correlations were established between the cognitive and activity components, which indicate the influence of the level of knowledge in the field of health preservation, information hygiene and security on the further behavior of adolescents in the information educational space.